1957
DOI: 10.2136/sssaj1957.03615995002100020001x
|View full text |Cite
|
Sign up to set email alerts
|

The Restoration of a Structurally Degenerated Soil1

Abstract: Common agricultural practices contribute to the loss of favorable soil structure. On the other hand, certain natural forces appear to contribute to the recovery of porosity and tilth. These include wetting and drying, freezing and thawing, the effects of root growth and decay, and the activity of soil organisms.In order to learn more about the nature and interplay of these forces, a method was developed for studying structural changes in buried cores of compacted soil. The technique of preparing these with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1972
1972
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…While the role of plants in creating various soil structural features is well known, the mechanisms involved have not been precisely defined or quantified. Some of the studies on this subject include those of Horn and Dexter (1989), Semmel et al (1990), Telfair et al (1957) and Terpstra (1989). There still remains need for more and better understanding of the mechanisms underlying the dynamics of aggregation by plant roots.…”
Section: Introductionmentioning
confidence: 99%
“…While the role of plants in creating various soil structural features is well known, the mechanisms involved have not been precisely defined or quantified. Some of the studies on this subject include those of Horn and Dexter (1989), Semmel et al (1990), Telfair et al (1957) and Terpstra (1989). There still remains need for more and better understanding of the mechanisms underlying the dynamics of aggregation by plant roots.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, W-D cycles can affect soil resistance measured by cone penetration, particle cohesion, internal friction, aggregate size and their mechanical stability (Rajaram and Erbach, 1999). These cycles can also result in aggregate formation in non-aggregated soils restoring the damaged structure of some soils (Telfair et al, 1957;Newman and Thomasson, 1979). According to Dexter (1988), W-D cycles affect directly soil aggregation due to the action of forces among soil particles and soil aggregates.…”
Section: Soil Structure Changes Due To Wetting and Drying Cyclesmentioning
confidence: 99%
“…Some authors have shown that sequences of W-D cycles can cause, for instance, aggregate formation in non-aggregated soils. It can in some circumstances regenerate structurally damaged soils and can induce, by increasing soil porosity, significant changes in SPS (Pagliai 1987, Sartori et al 1985, Newman and Thomasson 1979, Telfair et al 1957.…”
Section: Luiz F Pires Et Almentioning
confidence: 99%